THE INFLUENCE OF LEARNING MANAGEMENT AND PEDAGOGIC COMPETENCE ON QUALITY OF WORK QUALITY OF TEACHERS OF SMP NEGERI 23 PESAWARAN - Siti Atikah; Juhri Abdul Muin; Ahmaludin Ahmaludin (University of Sang Bumi Ruwa Jurai, 2023)
Learning management can be said to be not optimal, this can be seen from the incomplete preparation of lesson plans. The pedagogic competence of teachers is still weak, as can be seen from the fact that there are still teachers who experience problems in compiling sets of learning activities. The purpose of this study was to determine the influence of learning management and pedagogical competence on the quality of teacher work. The hypothesis in this study is that there is an influence of learning management and pedagogic competence either partially or simultaneously on the quality of teacher work. The sample in this study amounted to 26 teachers. Data collection techniques include observation, documentation and questionnaires. Methods of data analysis using a quantitative approach with the help of statistical tools SPSS version 21.0 includes the calculation of validity tests, reliability tests, simple and multiple linear regression tests, t tests, F tests and tests of the coefficient of determination. The results of hypothesis testing show that learning management partially has a positive influence on work quality with a contribution of 63.8percent. Pedagogic competence has a positive influence on work quality with a contribution of 18.2percent. Simultaneous hypothesis testing shows that learning management and pedagogic competence together have a positive influence on performance with a contribution of 64.5percent, while the remaining 35.5percent is a variation of other variables outside this study.